Upaya Pengembangan Profesionalisme Guru Sekolah Dasar - Natsir B. Kotten (Universitas Negeri Malang, 2016)
This study aims to find out information abaut the efforts of primary schools and the role of leaders in developing teacher professionalism. Using a qualitative approach, this study involved principals, teachers, and staffs of Education Department. The data were collected through observation, documentary study, in-depth interviews, and focused-group discussions, which were then analized by means of reduction, classification, and verification. The study found that primary schools carried out training and workshop, teacher group work, and classroom supervision for teacher professional development and that leaders played important roles in such activities.